Academic Approaches to Strengthening Students' Entrepreneurial Skills - , S.R. Padma (Archives of Current Research International, 2025)
Aim: Explore the academic approaches to strengthen the students’ entrepreneurial skills. Research Design: Descriptive study. Sample: Post graduate and Doctoral scholars of University. Methodology: A structured questionnaire was developed and applied as data collection tool to 751 students for this study. Results: Hosting training sessions led by successful entrepreneurs to impart essential skills, Creating hands-on learning opportunities for students to gain practical experience, Organizing workshops focused on enhancing creative thinking and brainstorming abilities, Organizing university-level conferences on entrepreneurship and Offering job placement services and vocational guidance were the mechanisms reported by the respondents. Regular curriculum revisions help align academic content with market demands while accommodating students' diverse abilities, ensuring education remains relevant and effective.